2012
DOI: 10.1038/onc.2012.258
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-24 regulates XIAP to reduce the apoptosis threshold in cancer cells

Abstract: MicroRNAs have been implicated as important mediators of cancer cell homeostasis, and accumulating data suggest compelling roles for them in the apoptosis pathway. X-linked inhibitor of apoptosis protein (XIAP) is a potent caspase inhibitor and an important barrier to apoptotic cell death, but the mechanisms which determine the diverse range of XIAP expression seen in cancer remains unclear. In this study, we present evidence that miR-24 directly targets the 3′UTR of the XIAP mRNA to exert translational repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 58 publications
1
67
0
Order By: Relevance
“…The ability of tumor cells to acquire chemoresistance is known to be via activation of cytoprotective processes against apoptosis, and therapeutically targeting these processes may be effective in overcoming chemoresistance (11)(12)(13). Our group as well as others has identified several miRNAs that can directly target cytoprotective processes, including the antiapoptosis pathway (XIAP, BIRC5), antioxidant activity (NRF2), and autophagy (ATG4, ATG7), and demonstrated that enforced expression of these miRNAs promotes drug-induced apoptosis in several human cancers (10,(37)(38)(39)(40)(41)(42)(43). On the other hand, clinical trials for miRNA therapy of liver and malignant hematopoietic cancers using a synthetic miR-34a mimic are currently ongoing (44,45).…”
Section: Discussionmentioning
confidence: 71%
“…The ability of tumor cells to acquire chemoresistance is known to be via activation of cytoprotective processes against apoptosis, and therapeutically targeting these processes may be effective in overcoming chemoresistance (11)(12)(13). Our group as well as others has identified several miRNAs that can directly target cytoprotective processes, including the antiapoptosis pathway (XIAP, BIRC5), antioxidant activity (NRF2), and autophagy (ATG4, ATG7), and demonstrated that enforced expression of these miRNAs promotes drug-induced apoptosis in several human cancers (10,(37)(38)(39)(40)(41)(42)(43). On the other hand, clinical trials for miRNA therapy of liver and malignant hematopoietic cancers using a synthetic miR-34a mimic are currently ongoing (44,45).…”
Section: Discussionmentioning
confidence: 71%
“…Therefore, we conclude that histone deacetylation has no or only minor effects on miR-24 expression. Xie et al (2013) also demonstrated that miR-24 expression is not altered by treatment with TSA or DAC (5-aza-20-deoxycytidine).…”
Section: Discussionmentioning
confidence: 87%
“…Later on, the same group [135] demonstrated that miR-34a and miR-34c, which are downregulated in NSCLC cell lines, could play a significant role in lung carcinogenesis by modulating the expression of PDGFR-α/β and thereby regulating TRAIL-induced cell death sensitivity. Another miRNA that can be involved in TRAIL resistance is miR-24 [136]. This miRNA directly downregulates the expression of XIAP and induces sensitivity to TRAIL-based therapy in TRAILresistant lung cancer cell line.…”
Section: Mirnas As Modulators Of Trail-based Therapymentioning
confidence: 99%